Multi-scale deformation characteristics and mechanism of red-bed mudstone in dry-wet environment - Yu, Fei; Tong, Kaiwen; Fu, Zhenghao; Feng, Gaoshun; Zhou, Zhe; Chen, Shanxiong; Dai, Zhangjun (Frontiers in Earth Science, 2022)
Repeated swelling-shrinking behaviors of red-bed mudstone poses a potential threat to high-speed railways. Through swelling test and dry-wet cycle test, the deformation law of mudstone samples was discussed. Using X-ray CT scanning, MIP and BET technology, the inner relationship between deformation and structural characteristics were clarified. The results showed that the surface of sample was chipped and peeled off after two cycles. During the dehumidification, the mudstone has undergone three stages of shrinkage adjustment, accelerated shrinkage and stable shrinkage. Uneven tensile stress caused by evaporation of water molecules in the initial stage of drying delayed the shrinkage. Initial water content was opposite to the changes of stable strain after water immersion and residual strain after dehydration, while it was positively correlated with environmental temperature. Porosity and connectivity keep increasing with the continuous cycle, and the number appeared to gradually descend from the two ends to the middle in space. Successive drying and wetting promoted a wider range of diameter-length ratio. Spatial orientation also transitioned to the polar angle. Specifically, the structure evolved from the layered shape to the tree-like and net-like in order. Microscopic scale mainly included uniform flat pores and wedge-shaped capillary pores, ranging from 10 to 80 Å. The number of cycles didn’t affect the morphology of micropores, but only caused volume and specific surface area to enlarge. The existence of clays generated irreversible deformation of micropores and initiated the gradual extension. This work will provide key data and necessary methods for the geohazard problems.